2021
DOI: 10.1016/j.jaci.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra combined with methylprednisolone in patients with severe COVID-19 pneumonia and hyperinflammation: An observational cohort study

Abstract: Background: Immunomodulants have been proposed to mitigate severe acute respiratory syndrome coronavirus 2-induced cytokine storm, which drives acute respiratory distress syndrome in coronavirus disease 2019 . Objective: We sought to determine efficacy and safety of the association of IL-1 receptor antagonist anakinra plus methylprednisolone in severe COVID-19 pneumonia with hyperinflammation. Methods: A secondary analysis of prospective observational cohort studies was carried out at an Italian tertiary healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 17 publications
1
104
1
3
Order By: Relevance
“…Nevertheless, various other clinical trials with anti-IL-6 receptor antibodies [ 32 ] concluded that mortality is subject to virtually a high state of hyper-inflammation. Bozzi et al [ 33 ] reported that IL-1 antagonists, such as anakinra, may have promising results in patients with high inflammation state towards survival and recovery from COVID-19. The authors of this study also concluded that treatment of COVID-19 patients with anakinra in combination with methylprednisolone may be beneficial for survival of patients on mechanical ventilators.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, various other clinical trials with anti-IL-6 receptor antibodies [ 32 ] concluded that mortality is subject to virtually a high state of hyper-inflammation. Bozzi et al [ 33 ] reported that IL-1 antagonists, such as anakinra, may have promising results in patients with high inflammation state towards survival and recovery from COVID-19. The authors of this study also concluded that treatment of COVID-19 patients with anakinra in combination with methylprednisolone may be beneficial for survival of patients on mechanical ventilators.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies on adult population affected by severe COVID-19 pneumonia are demonstrating the effectiveness of IL-1 blockade in reducing oxygen requirement and mechanical invasive ventilation as well as a significantly rapid improvement of patient's clinical conditions and reduction of inflammatory markers (27,28). Furthermore, an Italian study reported the efficacy of treatment with anakinra as add-on therapy to glucocorticoids in reducing the mortality of adult patients with severe COVID-19 pneumonia and hyperinflammation with a good safety profile (29). Our experience was in line with these recent evidences.…”
Section: Discussionmentioning
confidence: 99%
“…Most of benefit is shown so far in cohorts of patients who are not under mechanical ventilation and who present signs of hyper-inflammation. Retrospective data of the efficacy of anakinra administered intravenously are coming from France and Italy analysing cohorts of 12 patients (13), 29 patients (14) and 65 (15) patients and using concurrent comparators. The minority of patients were under mechanical ventilation and anakinra treatment provided survival benefit after 28 days.…”
Section: Discussionmentioning
confidence: 99%